Perceptions of e-cigarettes: a comparison of adult smokers and non-smokers in a Mechanical Turk sample. (4th May 2017) - Bauhoff, Sebastian; Montero, Adrian; Scharf, Deborah
ABSTRACT: Background : Given plans to extend its regulatory authority to e-cigarettes, the Food and Drug Administration (FDA) urgently needs to understand how e-cigarettes are perceived by the public. Objectives : To examine how smoking status impacts adult perceptions and expectations of e-cigarettes. Methods : We used Mechanical Turk (MTurk), a "crowdsourcing" platform, to rapidly survey a large ( n = 796; female = 381; male = 415), diverse sample of adult ever (44%) and never smokers (56%), including ever (28%) and never (72%) users of e-cigarettes. Results : Smokers and non-smokers learned about e-cigarettes primarily through the internet and conversations with others. Ever smokers were more likely than never smokers, and female current smokers were more likely than female former smokers, to have learned about e-cigarettes from point of sale advertising ( p 's < 0.05) and to believe that e-cigarettes help smokers quit ( p s < 0.05). Among never users of e-cigarettes, current smokers were more likely than never smokers and former smokers to report that they would try e-cigarettes in the future ( p s < 0.01). Current smokers' top reason for wanting to try e-cigarettes was to quit or reduce smoking (56%), while never and former smokers listed curiosity. In contrast, female current smokers' top reason for not trying e-cigarettes was health and safety concerns (44%) while males were deterred by expense (44%). Conclusions : Adult smokers and non-smokers have different perceptions and expectations of e-cigarettes. Public health messages regarding e-cigarettes may need to be tailored separately for persons with and without a history of using conventional cigarettes. Tailoring messages by gender within smoker groups may also improve their impact.